Carbamylated Erythropoietin Ameliorates Cyclosporine Nephropathy without Stimulating Erythropoiesis - Toyofumi Abe; Yoshitaka Isaka M.D., Ph.D.; Ryoichi Imamura; Yoichi Kakuta; Masayoshi Okumi; Koji Yazawa; Naotsugu Ichimaru; Hidetoshi Tsuda; Norio Nonomura; Shiro Takahara; Akihiko Okuyama (Cell Transplantation, 2012)
The introduction of cyclosporine (CsA) has improved graft survival, but it causes nephropathy, which limits its clinical utility. Recently, we reported that carbamylated erythropoietin (CEPO) protected kidneys from ischemia reperfusion injury as well as EPO. To investigate the clinical applications of CEPO, we next evaluated the long-term therapeutic effect of CEPO using a CsA-induced nephropathy model. CsA caused renal dysfunction, while EPO/CEPO administration significantly improved renal function. EPO treatment significantly increased Hb concentration, while CEPO treatment neither enhanced nor reduced Hb concentration. CsA treatment induced tubular apoptosis, while EPO/CEPO administration inhibited it and increased PI3 kinase activation and Akt phosphorylation. In parallel, morphological assessment revealed that EPO/CEPO significantly reduced CsA-induced interstitial fibrosis and inhibited interstitial macrophage infiltration. In addition, real-time RT-PCR demonstrated that cortical mRNA levels of TGF-β1 and type I collagen were suppressed in the EPO/CEPO group. These results suggest a new therapeutic approach using CEPO to protect kidneys from CsA-induced nephropathy.